2003 Handbook of Employment Regulations Affecting Florida Farm Employers and Workers: Plant Closing Notification / Layoffs (WARN Act) [Federal] - Leo C. Polopolus; Michael T. Olexa; Fritz Roka; Carol Fountain (EDIS)
The purpose WARN Act is provide employees with notification of intended layoffs or shut-down. This is EDIS document FE410, a publication of the Department of Food and Resource Economics, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida, Gainesville, FL. Published July 2003. This information is included in Circular 1200, Handbook of Employment Regulations Affecting Florida Farm Employers and Workers.